Inactive enzymatic mutant proteins (phosphoglycerate mutase and enolase) as sugar binders for ribulose-1,5-bisphosphate regeneration reactors - De, Dinesh; Dutta, D.; Kundu, M.; Mahato, S.; Schiavone, M. T.; Chaudhuri, S.; Giri, Ashok P.; Gupta, Vidya; Bhattacharya, S. K. (Microbial Cell Factories, 2005)
Background: Carbon dioxide fixation bioprocess in reactors necessitates recycling of D- ribulose1,5-bisphosphate (RuBP) for continuous operation. A radically new close loop of RuBP regenerating reactor design has been proposed that will harbor enzyme-complexes instead of purified enzymes. These reactors will need binders enabling selective capture and release of sugar and intermediate metabolites enabling specific conversions during regeneration. In the current manuscript we describe properties of proteins that will act as potential binders in RuBP regeneration reactors. Results: We demonstrate specific binding of 3-phosphoglycerate (3PGA) and 3-phosphoglyceraldehyde ( 3PGAL) from sugar mixtures by inactive mutant of yeast enzymes phosphoglycerate mutase and enolase. The reversibility in binding with respect to pH and EDTA has also been shown. No chemical conversion of incubated sugars or sugar intermediate metabolites were found by the inactive enzymatic proteins. The dissociation constants for sugar metabolites are in the micromolar range, both proteins showed lower dissociation constant (Kd) for 3-phosphoglycerate ( 655 - 796 mu M) compared to 3-phosphoglyceraldehyde ( 822 - 966 mu M) indicating higher affinity for 3PGA. The proteins did not show binding to glucose, sucrose or fructose within the sensitivity limits of detection. Phosphoglycerate mutase showed slightly lower stability on repeated use than enolase mutants. Conclusions: The sugar and their intermediate metabolite binders may have a useful role in RuBP regeneration reactors. The reversibility of binding with respect to changes in physicochemical factors and stability when subjected to repeated changes in these conditions are expected to make the mutant proteins candidates for in-situ removal of sugar intermediate metabolites for forward driving of specific reactions in enzyme-complex reactors.

Identification of Indian pathogenic races of fusarium oxysporum f. sp ciceris with gene specific, ITS and random markers - Gurjar, Gayatri; Barve, Maneesha; Giri, Ashok P.; Gupta, Vidya (Mycologia, 2009)
In this study we demonstrate the synergistic use of gene-specific markers, ITS-RFLP, ISSR and AFLP for distinguishing Indian F. oxysporum f. sp. ciceris races. We also report for the first time that F. oxysporum f. sp. ciceris race 3, a wilt pathogen of chickpea in India, is actually E proliferatum based on phylogenetic analysis with EF-1 alpha sequence data. E oxysporum f. sp. ciceris races 1, 2 and 4 were easily distinguished from ``race 3'' (F. proliferatum) by PCR amplification with oligonucleotides designed from conserved regions of Hop78 transposon (Hop 78), cutinase (Cut), desaturase (Dst). F oxysporum f. sp. ciceris race 4 was distinguished with the xylanase 3 (xyl3) gene by absence of amplification product only in this race. The Xyl3 amplified-DNA fragment isolated and sequenced from E oxysporum f. sp. ciceris race I was similar to the F-xylanase (Xyl3) gene of E oxysporum f. sp. lycopersici. A TELD motif, which is characteristic of the F-xylanases family, was detected within the deduced amino acid sequence of F. oxysporum f. sp. ciceris. Similarly the F oxysporum f. sp. ciceris Hop78 DNA fragment, which identified ``race 3'' (E proliferatum), was homologous to the Hop78 transposon of E oxysporum f. sp. melonis, including the 100 amino acid conserved domain and the characteristic CCHC motif. The internal transcribed spacer region-restriction fragment length polymorphism (ITS-RFLP) approach along with intersimple sequence repeat (ISSR) method also differentiated ``race 3'' (F. proliferatum). Races 1 and 2 were identified by unique AFLP patterns. Sequence characterization of race-specific AFLP products revealed significant homologies of these sequences with metabolically important genes.
Keywords: AFLP; F. oxysporum f. sp ciceris races; gene specific amplification; ISSR; ITS-RFLP; race delineation; sequence characterization; translation elongation factor (EF-1 alpha)

Identification and functionality prediction of pathogenesis-related protein 1 from legume family - Tellis, Meenakshi; Mathur, Monika; Gurjar, Gayatri; Kadoo, Narendra; Gupta, Vidya (Proteins-Structure Function and Bioinformatics, 2017)
The production and accumulation of pathogenesis-related (PR) proteins in plants is one of the important responses to biotic and abiotic stress. Large number of identified PR proteins has been categorized into 17 functional families based on their structure, phylogenetics, and biological activities. However, they are not widely studied in legume crops. Using 29 PR1 proteins from Arabidopsis thaliana, as query, here we have predicted 92 candidate PR1 proteins through the PSI-BLAST and HMMER programs. These candidate proteins were comprehensively analyzed with, multiple sequence alignment, domain architecture studies, signal peptide, and motif extraction followed by phylogenetic analysis. Further, response of two candidate PR1 proteins from chickpea against Fusarium oxysporum f.sp.ciceri attack was validated using qRT-PCR followed by their 3D structure prediction. To decipher mode of action for PR1s, docking of pathogen extracellular matrix components along with fungal elicitors was performed with two chickpea PR1 proteins. Based on these findings, we propose carbohydrate to be the unique pathogen-recognition feature for PR1 proteins and beta-glucanase activity via beta-glucan binding or modification.